2020
DOI: 10.3390/ijms21051731
|View full text |Cite
|
Sign up to set email alerts
|

Differential Cytotoxicity Induced by Transition Metal Oxide Nanoparticles is a Function of Cell Killing and Suppression of Cell Proliferation

Abstract: The application of nanoparticles (NPs) in industry is on the rise, along with the potential for human exposure. While the toxicity of microscale equivalents has been studied, nanoscale materials exhibit different properties and bodily uptake, which limits the prediction ability of microscale models. Here, we examine the cytotoxicity of seven transition metal oxide NPs in the fourth period of the periodic table of the chemical elements. We hypothesized that NP-mediated cytotoxicity is a function of cell killing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…95 In addition, the S/G2 transition is a crucial regulatory step to determine the timing of mitosis, which based on the successful DNA synthesis. The induction of cell cycle arrest in S phase by mixed-form nano-TiO 2 indicated that the particles may directly damage DNA or influence DNA replication machinery, 96 and it can also be attributed to the S-phase arrest caused by anatase-form nano-TiO 2 that we observed in cancer cells, since the mixed-form nano-TiO 2 is formed by rutile and anatase. We speculated that the decrease in the percentage of G0/G1 phase cells caused by mixed-form nano-TiO 2 may be related to the induction of S-phase arrest.…”
Section: Discussionmentioning
confidence: 67%
“…95 In addition, the S/G2 transition is a crucial regulatory step to determine the timing of mitosis, which based on the successful DNA synthesis. The induction of cell cycle arrest in S phase by mixed-form nano-TiO 2 indicated that the particles may directly damage DNA or influence DNA replication machinery, 96 and it can also be attributed to the S-phase arrest caused by anatase-form nano-TiO 2 that we observed in cancer cells, since the mixed-form nano-TiO 2 is formed by rutile and anatase. We speculated that the decrease in the percentage of G0/G1 phase cells caused by mixed-form nano-TiO 2 may be related to the induction of S-phase arrest.…”
Section: Discussionmentioning
confidence: 67%
“…The included studies used differing methods in assessing cytotoxicity and genotoxicity: cell membrane integrity was assessed with Lactate dehydrogenase (LDH) assays [ 44 , 57 , 116 ]; cell viability was assessed using tetrazolium reduction assays [ 82 , 83 , 90 , 116 ]; apoptosis was assessed using immunohistochemistry biomarkers [ 60 , 65 , 86 ]; electron microscopy was used to assess intracellular localisation of nanoparticles [ 34 , 106 ]; and cell inflammation was estimated using chemokines biomarkers (i.e., IL-8, TNF- α, and IL-6) [ 146 ]. Compounds such as MTT, XTT, MTS, and WST-1 are used to detect viable cells [ 147 ].…”
Section: Discussionmentioning
confidence: 99%
“…For cytotoxicity assay using SRB dye (Tolliver et al, 2020); cells were seeded in each well of 96-well plate at a seeding density of 0.5*10 4 per well in a 100 µL culture medium. The plate was then incubated for 24 hours at 37 °C in a 5 % CO2 incubator.…”
Section: ) Cell Line and Cytotoxicity Studymentioning
confidence: 99%